A relation between HLA antigens and clinical features in patients with acquired valvular heart disease. Issue 6024 (19th June 1976) - Ward, C; Gelsthorpe, K; Doughty, R W
Abstract : Analysis of the HLA antigen patterns in patients with acquired valvular heart disease showed that antigens A29 and AW30/31 occurred more often in those patients whose valvular disease was not preceeded by a history of rheumatic fever or chorea. Patients with no rheumatic history but with antigen A29 or AW30/31 had clinical features that distinguished them from others with valvular disease--namely, (a) isolated mitral valve disease and (b) the need for surgery, often at an early age, after a relatively short duration of symptoms.